The stances of Sultan Qaboos on the First Gulf War (1980–1988) - Mohammad Al Shuaili (Cogent Arts & Humanities)
The foreign policy of Oman, since Sultan Qaboos bin Said’s accession to the throne in 1970 until his death in 2020, has been characterized by vigorous activities and broad outreach during a period marked by significant global challenges and shifts across political, economic, and security dimensions. This was especially pronounced in the Arabian Gulf region, which endured a destructive conflict that jeopardized its security and economic stability, resulting in substantial costs. This conflict, the Iran-Iraq War, also known as the First Gulf War (1980–1988), posed a considerable threat. This study examines Sultan Qaboos bin Said’s position on this war and Oman’s foreign policy approach to managing its implications.